Spatial organization of genome architecture in neuronal development and disease. (October 2018) - Fujita, Yuki; Yamashita, Toshihide
Abstract: Although mammalian genomes encode genetic information in their linear sequences, their fundamental function with regard to gene expression depends on the higher-order structure of chromosomes. Current techniques for the evaluation of chromosomal structure have revealed that genomes are arranged at several hierarchical levels in three-dimensional space. The spatial organization of genomes involves the formation of chromatin loops that bypass a wide range of genomic distances, providing a connection between enhancers and chromosomal domains. Furthermore, they form chromatin domains that are arranged into chromosome territories in the three-dimensional space of the cell nucleus. Recent studies have shown that the spatial organization of the genome is essential for normal brain development and function. Activity-dependent alterations in the spatial organization of the genome can regulate transcriptional activity related to neuronal plasticity. Disruptions in the higher-order chromatin architecture have been implicated in neuropsychiatric disorders, such as cognitive dysfunction and anxiety. Here, we discuss the growing interest in the role of genome organization in brain development and neurological disorders. Highlights: The spatial organization of the genome and its role in transcriptional regulation are introduced. We focus on the changes in nuclear architecture in neural plasticity and development. Disruption of the three-dimensional genome structure causes neurological disorders.